2019
DOI: 10.2298/abs190131030k
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and biochemical profile of Azolla pinnata and Azolla caroliniana grown under greenhouse conditions

Abstract: This study aimed to evaluate the growth performance, pigment content changes, essential amino acids (EAAs), fatty acids (FAs), and proximate composition of Azolla pinnata and Azolla caroliniana grown in a greenhouse. Plants were grown in nitrogen-free Hoagland's solution at 28±2°C/21±2°C, day/night temperature and 60-70% humidity and examined on the 3 rd , 5 th , 10 th and 15 th days. The mean percentage of plant growth and relative growth rate for A. pinnata were 119% and 0.148 gg-1 day-1 , respectively, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
7
2
Order By: Relevance
“…The growth rate of Azolla in this study was slightly lower than the result of Hossain et al (2021) andda Silva et al (2022), who applied synthetic fertilizer in their research. However, it was higher than the results of research by Nordiah et al (2012), by growing Azolla only on the water without fertilizer, and those of Kösesakal and Yildiz (2019), with the application of Hoagland solution as fertilizer. This study further confirms that the requirement of various nutrition for Azolla production and it's availability in quail manure seem to match in order to grow Azolla under suitable environmental conditions.…”
Section: Relative Growth Ratecontrasting
confidence: 63%
“…The growth rate of Azolla in this study was slightly lower than the result of Hossain et al (2021) andda Silva et al (2022), who applied synthetic fertilizer in their research. However, it was higher than the results of research by Nordiah et al (2012), by growing Azolla only on the water without fertilizer, and those of Kösesakal and Yildiz (2019), with the application of Hoagland solution as fertilizer. This study further confirms that the requirement of various nutrition for Azolla production and it's availability in quail manure seem to match in order to grow Azolla under suitable environmental conditions.…”
Section: Relative Growth Ratecontrasting
confidence: 63%
“…The 15% Hoagland solution achieved a comparable growth rate of 0.190 day −1 . This contrasted to the research of [33], in which the optimal growth rate of 0.124 day −1 was achieved using a full strength Hoagland solution. The lowest growth rate was 0.123 day −1 , which was achieved using the 1% Hoagland solution.…”
Section: Resultsmentioning
confidence: 78%
“…The increase in growth rate for the 60% humidity compared to the 75% humidity was 5.8%, 2.4%, 1.2%, and 4.4%. There were two growth studies that reported humidity values: one reported 60% to 70% [33] humidity and the second reported 55% to 70% humidity [34]. Both studies reported the lower growth rates of 0.124 day −1 and 0.100 day −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our result on the Azolla growth rate is comparable to that reported in the references. For example, Kösesakal and Yıldız [48] reveal that A. pinnata has a growth rate of 0.148 g.g -1 .d -1 and 0.120 g.g -1 .d -1 for A. caroliniana. In addition, [42] reports a higher growth rate of 0.162 to 0.214 g.g -1 .d -1 with the highest value for Azolla cultivated without fertilizer addition.…”
Section: Day Of Measurementsmentioning
confidence: 99%